Offline Handwriting Character Recognition (for use of medical purpose) Using Neural Network (International Journal of Engineering and Computer Science, 2018)
Handwriting recognition means to scribe the written words from the paper. The written words are taken from the paper by the means of OCR. OCR means Optical Character Recognition. It is a technique of getting the printed or written text from the paper by using any scanning hardware like camera or scanner which can get printed or written words from the paper and convert it digitally. Offline handwriting recognition uses the techniques of OCR and able to detect and analyze the handwriting words. Here we can recognize the handwriting of the doctor and try to get some pattern which will be used to guess the most probable prescribed medicine. We can only guess prescribed medicine’s name and does not assure the exact name because we all know that it is difficult to read the handwriting of doctors for non-medicine personal.